Wild Oats : sowing vs. reaping - Shefsky, Lloyd E., (SAGE knowledge. Cases., 2016)
The case highlights Mike Gilliland, who built a single organic foods store in 1987 in Boulder, Colorado, into Wild Oats Markets, a chain of natural foods stores that by 2001 had annual sales of $1 billion and stores in 38 states. The case includes a history of the natural foods business and explores why Gilliland's timing was so favourable.